Statistical Resoning Student In Statistical Problem Based On Sex Differences - Luthfaturrohmah Luthfaturrohmah; Rooselyna Ekawati; Endah Budi Rahaju (SAINTIS Publishing, 2019)
The purpose of this study is to describe the level of statistical reasoning of male students in statistical problems, and describe the level of statistical reasoning of female students in statistical problems. The method used in this study is descriptive qualitative which describes the level of statistical reasoning of male and female students in statistical problems solving. The results of his research are there are differences in the level of statistical reasoning of male and female students in solving statistical problems. There are differences in the level of statistical reasoning between male and female students in the statistical reasoning process. Differences in the level of statistical reasoning between male and female students in the process of analyzing and interpreting data. Male students at level 4 and female students at level 5, whereas in the process of describing data, organizing data and replicating data on male and female students are at the same level. In describing data on male and female students at level 4, in the organizing process data on male and female students at level 3, in the process of representing data on male and female students at level 5.